2022
DOI: 10.1371/journal.pone.0266583
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods study of community-based health insurance enrollment trends and underlying challenges in two districts of northeast Ethiopia: A proxy for its sustainability

Abstract: Background The term "community-based health insurance" refers to a broad range of nonprofit, prepaid health financing models designed to meet the health financing needs of disadvantaged populations, particularly those in the rural and informal sectors. Due to their voluntary nature, such initiatives suffer from persistently low coverage in low- and middle-income countries. In Ethiopia, the schemes’ membership growth has not been well investigated so far. This study sought to examine the scheme’s enrollment tre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
2
0
0
Order By: Relevance
“…The authors of [6][7][8][9] suggested that variables related to medical personnel attitudes towards NHIS enrolees are related to socioeconomic and healthcare plans. The IDI finding was also consistent with enrolees' low-level satisfaction with medical personnel attitudes in Ghana [21] and Kallu, Ethiopia [22].…”
Section: Discussionsupporting
confidence: 73%
“…The authors of [6][7][8][9] suggested that variables related to medical personnel attitudes towards NHIS enrolees are related to socioeconomic and healthcare plans. The IDI finding was also consistent with enrolees' low-level satisfaction with medical personnel attitudes in Ghana [21] and Kallu, Ethiopia [22].…”
Section: Discussionsupporting
confidence: 73%
“…It is noteworthy that even though the JKN covered the medical bills, the patient chose not to attend further outpatient follow-up, possibly due to concerns about taking work leave. Similar cases of indirect financial problems by insurance-enrolled patients were noted in Ethiopia [ 13 ]. This case underscores the importance of addressing multifaceted challenges within the healthcare system to ensure timely and equitable access to essential medical care.…”
Section: Discussionsupporting
confidence: 62%